Consensus recommendations on balancing educational opportunities and service provision in surgical training: Association of Surgeons in Training Delphi qualitative study. (December 2020) - Pucher, Philip H.; Peckham-Cooper, Adam; Fleming, Christina; Mohamed, Walid; Clements, Joshua Michael; Nally, Deirdre; Humm, Gemma; Mohan, Helen M.; ,
Abstract: Background: Ensuring the highest quality of surgical training remains a challenge as demands on health service provision rise. This study aimed to explore the differences and potential conflicts between service provision and dedicated training activity provided by surgical trainees, and recommend solutions. Methods: Participants were drawn from the Association of Surgeons in Training (ASiT) national council. Nominal Group Technique (NGT) was employed by members of the ASiT executive addressing 3 key domains (1) defining differences between training and service tasks, (2) impact of service-provision on training and (3) ways to improve training. A two-round Delphi process was conducted via electronic survey to ASiT council. Consensus was considered achieved for any statement where 80% or more of respondents indicated agreement. Results: 47 statements were generated through NGT which were put to the Delphi process. Consensus was reached on a total of 24/47 statements. Educational or training tasks were identified as being activities which progressed a trainee's skill set, could be tailored to a trainee's own ability, and involved acting as a trainer to more junior colleagues. The negative impact of excess service provision included training quality, trainee mental health, and surgical trainee recruitment. Potential measures to improve training included increasing hospital staffing and resources, protected training times, trainee-specific or competency-based learning and training or incentivising trainers. Conclusion: This trainee-based study provides several consensus recommendations on the characteristics that define surgical training and how a balance between service provision and training can potentially be achieved. Policy makers and health systems may be guided by these to ensure high quality training and a satisfied workforce. Highlights: Trainee consensus was reached on differentiating service provision from training. Training tasks are exemplified by trainee skill progression, with tasks suited to trainee ability and competency. Training imbalances may have a negative impact on mental health, trainee retention, recruitment to specialty. A number of cultural, organisational, and procedural solutions are recommended to improve training.